Aspirin nonsensitivity in patients with vascular disease: Assessment by light transmission aggregometry (aspirin nonsensitivity in vascular patients) - Hamzah Khan; Abdelrahman Zamzam; Reid C. Gallant; Muzammil H. Syed; Margaret L. Rand; Heyu Ni; Thomas L. Forbes; Mohammed Al‐Omran; Mohammad Qadura (Research and Practice in Thrombosis and Haemostasis, 2021)
Abstract Background Aspirin is a key antiplatelet therapy for the prevention of thrombotic events in patients with cardiovascular disease. Studies suggest that ≈20% of patients with cardiac disease suffer from aspirin nonsensitivity, a phenomenon characterized by the inability of 81 mg aspirin to inhibit platelet aggregation and/or prevent adverse cardiovascular events. Objectives To investigate aspirin nonsensitivity in patients with vascular disease and assess the consequences of aspirin nonsensitivity. Methods One hundred fifty patients presenting to St. Michael’s Hospital’s outpatient clinics with evidence of vascular disease (peripheral arterial disease or carotid artery stenosis) and a previous prescription of 81 mg of aspirin were recruited in this study. Light transmission aggregometry with arachidonic acid induction was used to determine sensitivity to aspirin. Patients with a maximum aggregation ≥20% in response to arachidonic acid were considered aspirin nonsensitive, as per previous studies. Results Of the 150 patients recruited, 36 patients (24%) were nonsensitive to 81 mg of aspirin. Of these 36 nonsensitive patients, 30 patients provided a urine sample for urine salicyluric acid analysis (a major metabolite of aspirin). Urine analysis demonstrated that 14 patients were compliant and 16 were noncompliant with their aspirin therapy. Major adverse cardiovascular events and major adverse limb events were significantly higher in the nonsensitive patients compared to sensitive patients (hazard ratio, 3.68; P < 0.001). Conclusion These data highlight the high prevalence of aspirin nonsensitivity and noncompliance in patients with vascular disease and emphasizes the urgent need for improved medical management options for this patient population.